To find the product of the polynomial expressions \((xy + 1)(x - 3)\), we'll use the distributive property (also known as the FOIL method for binomials):
\[ (xy + 1)(x - 3) = xy \cdot x + xy \cdot (-3) + 1 \cdot x + 1 \cdot (-3) \]
Calculating each term:
- \(xy \cdot x = x^2y\)
- \(xy \cdot (-3) = -3xy\)
- \(1 \cdot x = x\)
- \(1 \cdot (-3) = -3\)
Now, combine all the terms:
\[ x^2y - 3xy + x - 3 \]
Thus, the final product of the polynomial expressions is:
\[ \boxed{x^2y - 3xy + x - 3} \]
This corresponds to the first option in the responses.